PKM IMPLEMENTASI APLIKASI PEMBELAJARAN INTERAKTIF PENGENALAN TATA SURYA BERBASIS CONSTRUCT 2 PADA SMP NEGERI 2 JIPUT - Gagah Dwiki Putra Aryono; Sigit Auliana; Asep Sapaatullah; Maman Masyhuri; Achmad Dwi Saputro (Merwinspy Publisher, 2025)
This Community Service Program (PKM) aims to implement an interactive learning application based on Construct 2 for introducing the solar system at SMP Negeri 2 Jiput. The application is designed to enhance students' understanding of the solar system through engaging and interactive visual approaches. The methods used in this activity include teacher training, application installation on school devices, and monitoring during the learning process. The expected outcomes are increased student interest and a deeper understanding of solar system concepts. This program is expected to positively impact the effectiveness of learning and promote the integration of information technology in the educational process.